Electro-retino-encephalography in Leber's tapeto-retinal dystrophy - Fırat, Tanju (The Turkish Journal of Pediatrics, 1969)
Electro-retinographic and electro-encephalographic investigations in Leber's tapeto-retinal dystrophy were carried out on 39 patients of different ages. In 92.3 per cent of the cases ERG was abolished, and in 33.4 per cent dysrhythmic changes of the parieto-occipital type were present in EEG. These results are similar to those of other authors, and emphasize once more the importance and value of ERG in the differential diagnosis of Leber's tapeto-retinal dystrophy.